The Performance of Family Firms During Crisis Periods: The Case of Greece - Kinias, Ioannis (European Journal of Family Business, 2022)
This paper examines the effect of the family involvement in the performance of Greek listed companies, during the Greek financial crisis. The involvement of family in firm’s ownership, management and governance along with the firm’s age constitute the unified framework that describe the family influence on the enterprise. The main contribution of this paper is the investigation of a research period when Greece faced an unprecedented economic 9 year crisis that affected all sectors of the economy, with 72% of listed companies showing a decrease in revenue and the total capitalization of the Greek Stock Exchange shrinking by 70%. No previous study has incorporated performance data on listed companies during a corresponding financial crisis with large fluctuations in all performance indicators and a high volatility in the national economy. The sample of the research includes 80 family firms listed in the Greek Stock Exchange. The findings illustrate a better performance for family firms with lower family ownership and prove a stronger performance in younger family businesses. The results of the study do not confirm the positive involvement of family members, through management (CEO) and governance (BoD) positions in the family business performance.